LOGISTIC MANAGEMENT IN THE IMPLEMENTATION OF EXPO REI 2025 BY PT. DEBINDO MEGA PROMO MAKASSAR - Tineza Olivia Lande; Nur Farah Fajriaty Muchlis; Almas Nabili Imanina (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This research aims to analyze the logistics management of Expo REI 2025 organized by PT. Debindo Mega Promo Makassar, focusing on planning, procurement, handling, and evaluation stages. Using a qualitative descriptive method, data were collected through interviews, observation, and documentation with key stakeholders such as project managers, logistics teams, and exhibitors. The results show that logistics management was carried out systematically through four stages. Planning emphasized scheduling, budgeting, and coordination with vendors. Procurement involved selection and contracting of suppliers to provide event needs, although incomplete specifications occasionally caused delays. Handling encountered challenges such as limited loading dock capacity, restricted time due to mall operations, and booth area violations by exhibitors. Solutions included staggered loading schedules, enhanced signage, and stronger coordination. Evaluation indicated improved efficiency compared to previous years, though communication gaps remained an issue. The research concludes that effective logistics management is crucial for the success of exhibitions. Recommendations include developing more detailed MoUs with vendors and exhibitors, improving communication during technical briefings, and adopting innovative approaches to logistics planning for future events